As a Chinese researcher in Belgium: Path dependence or path-breaking? - Fan Xiao (Belgeo)
Extra-regional linkages contribute to innovation. However, detailed thoughts of innovators are missing in the literature. A question arises: how does a newly established extra-regional linkage affect knowledge production? To address this question, as a Chinese researcher in Belgium, I use my own surrounding experience to explore the drivers of innovation types in this essay. The findings show that: to some extent, utilitarianism and neoliberalism contribute to path dependence of knowledge production, while weak local embeddedness in the two countries of ours leads to path-breaking. Then, I show my concerns that path dependence might lead to (re-)colonial turn of knowledge production worldwide. Hopefully, this essay can broaden our understanding of the microscopic innovation process.